Association Between Hormonal Birth Control, Substance Use, and Depression - Newman, Sharlene D. (Frontiers in Psychiatry, 2022)
Objective The current study examined the impact of the use of hormonal birth control, cannabis (CB), and alcohol on depression symptoms. Study Design Survey data from 3,320 college-aged women collected over a 2-year period. Depression symptoms were assessed using the PHQ-9. Results Individuals taking hormonal birth control (N = 998; age = 19.1 ± 1.6 years) had lower overall depression scores than did those not taking birth control (N = 2,322; age = 19.1 ± 1.8 years) with 15.2% of those not taking hormonal birth control had depressive symptoms while 12.1% of those in the birth control group had depressive symptoms. Additionally, those taking hormonal birth control had higher scores on the alcohol and CB use assessment. A between-subjects ANOVA with depression score as the dependent variable found significant effects hormonal birth control use, CB and alcohol use, as well as a significant interaction between CB use and hormonal birth control use. Conclusions While there are some limitations (e.g., the between subjects design makes it such that there may be uncontrolled differences between groups), the results suggest that hormonal birth control use may help to reduce depressive symptoms. Implications More studies examining the impact of hormonal birth control and substance use on depression are required. The results suggest a potential interaction between CB and hormonal birth control use on depression symptoms that is not observed for alcohol. This implies that alcohol and CB may be linked to depression via different mechanisms.